Superconductor fault current limiter effect on the performance of doubly-fed induction generators - Farzaneh Mohammadi; Mohammad Molaei (Institute of Advanced Engineering and Science, 2020)
Between different wind turbine-generator configurations, one of the most accepted and highly regarded structures in the industry is the wind turbine with doubly-fed induction generator. The DFIG wind turbines are very sensitive to grid disturbances especially to voltage drop during grid faults due to relatively low power of the power converters. Fault in a power system causes voltage drop, current increase in stator and rotor coils, and over voltage in the DC shin. Several control methods have been proposed so far. A model based on power electronic instruments and superconductor theory, superconductor fault current limiter (SCFCL), has been proposed in this paper to improve domain and the attenuation time of the parameters under control such as voltage, current, and speed and voltage of the DC link against various types of faults (single-phase, two-phase, and three-phase). In addition to this, in order to compare the results with convectional models (crowbar) and study the innovation of the proposed model, a simulation of the system under two-phase fault and use of crowbar method to control the fault has been conducted using MATLAB-SIMULINK and also, the performance of the proposed method has been assessed.